Cobalt-Containing Dispersion Catalysts for Three-Phase Fischer–Tropsch Synthesis - Maximov, Anton Lvovich; Kulikova, Mayya Valerevna; Dementyeva, Oksana Sergeevna; Ponomareva, Anna Konstantinovna (Frontiers in Chemistry, 2020)
Nanosized catalyst dispersions have significant potential for improving hydrocarbon production from carbon monoxide and hydrogen via Fischer–Tropsch synthesis, an essential alternative to the use of petroleum as a raw material. New dispersed cobalt catalysts and dispersed-phase cobalt-based catalysts with Pd, Al2O3, or ZrO2 additives for the Fischer–Tropsch synthesis were synthesized in the present work. A dispersed cobalt phase was prepared in a heavy paraffin medium using ex situ and in situ approaches through thermal decomposition of a nitrate precursor at various temperatures. Analyses showed that an increase in the temperature for catalytic suspension formation from 215 to 260°C enlarged the particles in the dispersed phase from 190 to 264 nm, which was probably due to increased agglomeration at elevated temperatures. The rheological properties of the obtained catalytic suspensions can be described by the Bingham equation. Furthermore, the concentration of the dispersed phase had a direct impact on the structure of the entire catalytic system. Ultrafine suspensions of palladium-promoted catalytic systems were tested for the Fischer–Tropsch synthesis. The overall yield of C5+ hydrocarbons was as high as 50 g/m3, and the productivity of the Pd-promoted catalytic systems reached 270–290 g/(kgCo · h).